PERSEPSI KONSUMEN TERHADAP IKLAN MOBIL AVANZA MELALUI MEDIA TELEVISI - Made Yeppi Herunda (Universitas Pendidikan Nasional, 2015)
study aims to analyze and to interpret consumer’s perception towardadvertisement of Avansa car version of tour around of Indonesia through television. Themethod has been applied for this study was qualitative descriptive approach with triangulationtechnique and in-depth interview to problem solving by conduct comprehending and collectdata in-whole and intact from research object in order to get focus overview from observationresult and observation from site.Conclusion of this study is the consumer’s perception toward advertisement of Avansacar through television media is positive match with message send from the advertisement. Allof this written in expression from some informant who declare that perception is near same butin different expression that is Avansa car is comfort car, many friends by meaning manyenthusiast or user, multi-function, many service post purchasing, its design is update, and havesome excellence like reachable price, saving fuel, and environment friendly.Keywords: Perception, Advertisement, and Television.